The Effects of Seasonal Prescribed Burning on Flint Hills Dung Beetle (Scarabaeinae) Populations - Herman Griese; Andrea Salazar; Victoria Pickens; Cassandra Olds (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:This study aimed to determine if the season of prescribed burning impacted dung beetle communities on pastures grazed by cattle in the Flint Hills. Study Description:Dung beetle populations at the Kansas State University Beef Stocker unit were sampled biweekly for three months over the summer grazing period to determine if beetle populations varied between spring, summer, or fall burned pastures. Results:At least eight species of dung beetles were identified with a total of 8,646 dung beetles collected. Dung beetle populations were not different (P>0.05) between spring, summer, and fall burned pastures although peak beetle populations were observed two weeks earlier in the spring burned pastures than summer and fall. The Bottom Line:Dung beetle populations were not impacted by the season of the burn and producers can select a burn season which best suits their needs without impacting dung beetle diversity or population density.
Keywords: dung beetles; prescribed burning; season